An Enhanced Aquila Optimizer-Based Distributed Generation Framework for Harmonic Mitigation - Adeyinka, I. M.; Abubakar, I.; Kadandani, N. B.; Sa’ad, M. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
This research work presents an improved Aquila optimizer-based distributed generation system for solving power quality problems. This is particularly important for mitigating the harmonics presence in a radial distribution system (RDS). The radial distribution network (RDN) was modeled in the presence of the nonlinear load (NLLD) and nonlinear distributed generation (NLDG). RDN provides a simple, cost-effective structure with a single power source that can be analyzed with a simplified forward/backward sweep load flow algorithm, making it easier to determine the optimal size and location of active power filters to mitigate harmonics and improve voltage quality. An improved Aquila optimization algorithm was then used to optimally size and place active power filters (APFs) in the adaptive RDN to control the harmonics, ensuring that the harmonics present in the system do not exceed IEEE-519 of 1992 standard limits. The results obtained from the developed scheme were presented and compared with the results obtained when Adaptive Grey Wolf Optimizer (AGWO) and Aquila Algorithm (AO) were used. THD and fitness function were used as the performance metrics. All simulations were carried out in the MATLAB/Simulink environment R2022b. The THD values obtained during various periods of the day were presented and it was observed that high distortions were recorded between hours 11 to 13, with the highest distortion occurring at hour 12. To further analyze the efficacy of the developed approach after placement of the APF in the IEEE 69-bus network, the result of the THD obtained when the improved Aquila algorithm was used for the placement of the APFs were presented. It was observed that the THD values obtained for the entire 69-bus network were well within the IEEE standard limit. Further, the results obtained from the developed scheme were compared with those obtained when AGWO and AO were used for harmonic mitigation in the distribution system. It was observed that the THD values obtained by the developed scheme outperformed those obtained from the AGWO technique by 5.96%, 4.71%, 3.47%, 32.79%, 3.62%, 11.68%, and 30.25%, respectively, for the bus numbers that have higher distortion values, while it also outperformed the Aquila algorithm by 3.07%, 2.41%, 1.88%, 31.97%, 1.84%, 16.88%, and 25.98%, respectively. The developed approach provides a practical and computationally efficient solution for harmonic mitigation and can be extended to larger and more complex power systems for improved grid performance.